Extraction and quantification of phycobiliproteins from the red alga Furcellaria lumbricalis - Saluri, Mihkel; Kaldmäe, Margit; Tuvikene, Rando (Algal research (Amsterdam), 2019)
Phycobiliproteins are natural additives in food industry and essential fluorescent probes in biotechnology. Various algal species may be suitable for their extraction, therefore, it is important to study different seaweeds to determine the highest-yielding species. Furcellaria lumbricalis, a red algal species primarily harvested from Canadian, Danish and Estonian waters, has been utilized for merely furcellaran extraction in Estonia on a commercial scale for over 50 years. To further valorize the bioresource it is vital to study whether additional products, such as phycobiliproteins, can be extracted. In the given study, optimal phycobiliprotein extraction conditions from F. lumbricalis were determined for the first time. For quantification, a novel high-pressure liquid chromatography method with fluorescence and photodiode array detection was developed. Considering R-phycoerythrin, citrate pH 6 buffer gave the highest yields (0.13% using fluorescence detector and 0.43% using photodiode array detector) after an extraction for 24 h at 20 °C. Different enzymes (cellulases, xylanases, galactosidases) and their combinations, lowering the extraction temperature or ultrasonication increased the yield further. In addition, red-coloured low-molecular fraction (with similar absorption characteristics to R-phycoerythrin) was separated. For allophycocyanin phosphate pH 6 buffer gave slightly higher yield (0.09% using fluorescence detector and 0.12% using photodiode array detector), compared to citrate or acetate buffer at the same pH. However, the tested enzyme combination, temperature variation and ultrasonication were not so advantageous for allophyocyanin recovery. The phycocyanin concentration from the red algae was below the limit of detection. [Display omitted] •Chromatography method with fluorescence and photodiode array detectors was developed.•Buffers at pH 6 give higher phycobiliprotein yields from Furcellaria lumbricalis.•Yields are increased at lower temperatures and with enzymolysis or ultrasonication.•Low molecular-weight fraction with akin absorption to phycoerythrin was obtained.•Phycocyanin is not detected in Furcellaria lumbricalis with the tested criteria.